Bandwidth allocation and Quality of Service (Qos) in ATM network / Nursyamshadiha Mohd. Yunus - Mohd. Yunus, Nursyamshadiha (2005)
There has been a growing interest in the development of integrated multi-service enterprise and service provider networks, which consolidate voice, video, imaging and computer data traffic into a single network. The driving forces for this interest are the rapid rate of growth in non-voice traffic, the emergence of new strategic multimedia applications, and the significant cost savings which can be realized from network consolidation. A common direction for both enterprises and service providers is the evolution towards ATM networking. This paper presents the application of ATM Network. ATM techniques are applied in creating broadband integrated networks, local area networks and exchanges. Bandwidth m1d QoS is the central theme of ATM.